2019
DOI: 10.1039/c9cc06256d
|View full text |Cite
|
Sign up to set email alerts
|

Beyond protein binding: recent advances in screening DNA-encoded libraries

Abstract: DNA-encoded libraries are usually screened against tagged proteins to identify ligands, but many other screening modalities either have been, or likely will be, developed that expand the utility of these libraries as a source of bioactive molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 68 publications
0
57
0
Order By: Relevance
“…Reduced diversity, less novelty Ensemble docking [235][236][237] Considering protein flexibility, improved enrichment factors, rescue of false-negative ligands Increased computational burden, pose evaluation, false positive Energy-based pose evaluation [248][249][250][251][252] Improved scoring and ranking ability Substantial computational burden, method validation target dependency 159,160,242 It was reported that a PAM of M2R is located above the orthosteric site and interacts with ECLs. Korczynska et al screened 4.6 million molecules against the allosteric sites of M2R and identified a PAM that potentiated the action of antagonist N-methyl scopolamine (NMS).…”
Section: Substantial Computational Resources Compound Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced diversity, less novelty Ensemble docking [235][236][237] Considering protein flexibility, improved enrichment factors, rescue of false-negative ligands Increased computational burden, pose evaluation, false positive Energy-based pose evaluation [248][249][250][251][252] Improved scoring and ranking ability Substantial computational burden, method validation target dependency 159,160,242 It was reported that a PAM of M2R is located above the orthosteric site and interacts with ECLs. Korczynska et al screened 4.6 million molecules against the allosteric sites of M2R and identified a PAM that potentiated the action of antagonist N-methyl scopolamine (NMS).…”
Section: Substantial Computational Resources Compound Synthesismentioning
confidence: 99%
“…Specifically, DEL has emerged as a powerful approach to drug discovery. [248][249][250][251] Created by split and pool synthesis, DEL usually contains hundreds of thousands to billions of distinct small molecule-DNA conjugates. A majority of DEL-based HTS reported to date involve incubation of an immobilized target protein with the library before the protein-ligand complexes are isolated.…”
Section: Novel Screening Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Many relevant pathologies/phenotypes are simply not affected through such interactions, as supported by the large number of DEL hits that ultimately have no activity in vitro or in vivo. [25,40] To this end, activity-based DEL selections that rely on more complex biochemical assays would be a powerful tool. Recently, Paegel and coworkers reported a microfluidics-based system that allows a one-bead-one-compound (OBOC) DEL to be selected for activity instead of merely binding ( Figure 3C).…”
Section: Selection Strategiesmentioning
confidence: 99%
“…Although expanding the proteome available to DEL selections is a valuable task, these protocols are inherently restricted to small molecule‐protein binding. Many relevant pathologies/phenotypes are simply not affected through such interactions, as supported by the large number of DEL hits that ultimately have no activity in vitro or in vivo . To this end, activity‐based DEL selections that rely on more complex biochemical assays would be a powerful tool.…”
Section: Selection Strategiesmentioning
confidence: 99%